Das ideias constituintes da noção de felicidade no de consolatione philosophiae - Leal, Lauro Cristiano Marculino (2016)
Reflecting on Boethius' thought is to bring with him the responsibility of reaching the intensity of his work, given that in addition to his contribution as one of the main translators and commentators, he will focus on the History of Philosophy as one that offered new directions and problems To be investigated, since, among other subjects, presented to society a new educational methodology, probably anticipating Scholasticism. He introduced in the philosophical discussions the problem of universals when he asked, in his commentary on Isagoge de Porfirio, the mode of existence of genera and species, he elaborated with notoriety works dealing with music, theology, mathematics, logic and metaphysics. However, the proposal of our research is to focus on one of his works of greatest repercussion in the medieval period and that offers, among various motes, a new meaning to the concept of happiness: The Consolation of Philosophy. This will then be a link between the Hellenic world, with its set of constituted philosophical systems and a new Roman cultural and social structure, in which the central theme that will make this junction is the idea of happiness. In this way, we will try to systematize the path that Boethius developed to demonstrate that the understanding of happiness is a way to free us from the anguish contained in false goods, whose implication will be to promote an approximation of what is true. Through this, we will explore the problems that originate in the very concept of happiness and its relation to freedom and justice, in order to stand out as fundamental elements that support the proposal of the book, presenting them as part of a basic structure, Whose analysis leads us to the understanding of the main questions that involve the condition of man's existence.